Development of an Evaluation System for Fusarium Resistance in Wheat Grains and Its Application in Assessment of the Corresponding Effects of Fhb1 - Gong, Xuan (Plant disease, 2020)
Fusarium head blight (FHB) caused by Fusarium species is a globally important wheat disease. Host resistance to FHB is composed of multiple mechanisms, including resistance to initial infection (type I), disease spread (type II), toxin accumulation (type III), kernel infection (type IV), and yield loss (type V), of which the last three have been less studied. Traditionally, the Fusarium-damaged kernel rate (FDK; percentage of Fusarium-infected grains) from point- or spray-inoculated experiments was used as the parameter for type IV resistance, which may be problematic because of the influence of type II resistance. Here we propose a new definition for type IV resistance: that is, the resistance against Fusarium infection expressed in wheat grains that have the same chance in contact with the pathogen, under favorable temperature and humidity for infection. Fhb1 confers strong type II resistance, leading to significantly reduced FHB severity and FDK. To investigate the role of Fhb1 in type IV resistance, a pair of near-isogenic lines, R22W (Fhb1 carrier, resistant in terms of type II resistance) and S22V (non-Fhb1, susceptible), along with eight wheat genotypes differing at Fhb1 were inoculated at different grain development stages with Fusarium macrospores both in vivo and in vitro. The in vivo experiments with all florets inoculated demonstrated a significant reduction in thousand kernel weight (TKW) in inoculated grains, regardless of their Fhb1 status and developmental stages. Surprisingly, R22W showed more TKW reduction than S22V, which was supported by the scanning electron microscopy observation that confirmed the more severe degradation of starch granules in R22W grains. The in vitro experiments demonstrated that grains from both R22W and S22V promoted fungal colonization, but no significant difference was found between the two lines. In summary, our results indicated that the proposed type IV evaluation system is effective in determining different grain resistance levels, providing novel tools for FHB resistance breeding. The finding that Fhb1 is not associated with type IV resistance enriches our understanding of this gene